EFEKTIVITAS MODEL CHILDREN LEARNING IN SCIENCE MENGGUNAKAN MEDIA MANIPULATIF UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI GERAK DAN GAYA - Ramadhani, Widya Santi; Fauza, Naila; Z, Fakhruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to examine the effectiveness of the Children Learning in Science (CLIS) model using manipulative media in improving student learning outcomes, and to determine the difference in learning outcomes between classes implementing the CLIS model and those using conventional learning on the subject of Motion and Force in Grade VII at SMPN 46 Pekanbaru. The research methodology employed was a quasi-experiment with a nonequivalent posttest-only control group design. The research sample consisted of 68 students divided into two groups: 34 students in class VII A as the control group and 34 students in class VII D as the experimental group. The research instrument was a learning outcome test consisting of 20 multiple-choice questions organized according to Bloom's Taxonomy cognitive levels (C1-C5), with the data subsequently analyzed through descriptive and inferential methods. The results showed that the average learning outcome for the control class was 70.44 (Good category), while the experimental class achieved an average of 81.91 (Very Good category). Consequently, there is a significant difference between the learning outcomes of students in the control and experimental classes, proving that the effectiveness of the Children Learning in Science model using manipulative media is capable of increasing student learning outcomes in the subject of Motion and Force compared to conventional learning.